The internationalization of energy supply structures - Heinz Jürgen Schürmann (Intereconomics, 1980)
The World Energy Conference will be held in Munich in mid-September. It will have to deal with diverse and complex problems of energy policy, for the seventies have presented tremendous challenges in the energy field. The control over oil—with 46% of the world supply still by far the most important source of energy—has been reorganized and two oil crises have exposed the flow of supplies to severe disruption and political hazards. As far as can be foreseen, the supply is unlikely to keep abreast of the world-wide rise of energy consumption. To replace the oil gradually will therefore be the major task in the energy field in the coming decades. What will be the supply position between now and the year 2000? And which structural changes will have to be effected?
Keywords: 330; Energy Policy